Influence of the Quality of Accrual Financial Report Information with the Roles of Accounting Information System as an Intervening Factor - Purwanti, Dyah; Natser, Ghulbudin Isham (Jurnal Dinamika Akuntansi, 2016)
This study aims to find empirical evidence about the role of accounting information system (AIS) as intervening factors that affect the quality of financial reporting information of the government. This study uses a questionnaire that primary data collected from respondents, namely employees of the accounting department of the government units, especially a partner institution in the State Treasury Office (KPPN) 2 Jakarta. Data processing is performed by the method of partial least squares (PLS). The results of this study are the accounting information system has significantly the impact on the quality of government financial reporting information. While the capacity factor of human resources, control data input and application of Government Accounting Standards (SAP) have a significant direct effect on the AIS, is larger when compared to a direct influence on the quality of financial reporting information. Other factors, organizational commitment and internal control system has a significant influence either directly or indirectly on the quality of financial reporting information. The findings of the study are expected to provide input to the government the importance of improving the accounting information system, such as strengthening the capacity of human resources and accounting applications in realizing quality financial information.